Respuesta :

If x + 3y = 1, then x = 1 - 3y.

Then in the second equation, replace x with 1 - 3y :

-x + 2y = 4

- (1 - 3y) + 2y = 4

-1 + 3y + 2y = 4

-1 + 5y = 4

5y = 5

y = 1   →   x = -2

since x = 1 - 3•1 = 1 - 3 = -2.

Alternatively, you can instead solve for y in the first equation, so that if x + 3y = 1, you get

x + 3y = 1

3y = 1 - x

y = (1 - x)/3

Then replace y in the second equation:

-x + 2y = 4

-x + 2 ((1 - x)/3) = 4

-x + 2/3 (1 - x) = 4

Multiply both sides by 3 to get rid of the fraction:

-3x + 2 (1 - x) = 12

-3x + 2 - 2x = 12

-5x + 2 = 12

-5x = 10

x = -2   →   y = 1

since y = (1 - (-2))/3 = (1 + 2)/3 = 3/3 = 1.